Integrating Interval Agreement Approach (IAA) with TOPSIS in Multi-Criteria Group Decision Making (MCGDM) - Nadia Madi, Elissa; Yusoff, Binyamin (International Journal of Engineering and Technology, 2018)
This paper presents a proposed method to integrate Interval Agreement Approach (IAA) with Technique for order performance by similarity to ideal solution (TOPSIS) for Multi-Criteria Group Decision Making (MCGDM). The proposed method utilises IAA to model the preferences (word) given by decision maker in the initial step of TOPSIS-MCGDM. In real world, problems preferences may be given as imprecise or incomplete information. An issue has been raised about how to precisely modelling the preferences or word in the context of MCGDM. One of the strengths in IAA technique during the modelling process is it distinguished the two types of uncertainties (intra- and inter-) in different degree of freedom. The proposed method is able to capture the information from one or more intervals (with crisp or uncertain interval endpoints) associated with preferences given by the decision maker. This paper provides an example to illustrate the application of the proposed model.Â Â